Chemical Constituents from Bombacopsis glabra (Pasq.) A. Robyns: Complete 1H and 13C NMR Assignments and X Ray Structure of 5-Hydroxy-3,6,7,8,4'-pentamethoxyflavone - Paula Vanderlúcia F.; Barbosa Luiz C. A .; Errington William; Howarth Oliver W.; Cruz Mariluze P. (Journal of the Brazilian Chemical Society, 2002)
The flavone 5-hydroxy-3,6,7,8,4'-pentamethoxyflavone (1) and the triterpenes lupenone, 9,19-cyclolanost-23-ene-3beta,25-diol (2), (24R)-9,19-cyclolanost-25-ene-3beta,24-diol (3) and (24S)-9,19-cyclolanost-25-ene-3beta,24-diol (4) were isolated from the hexane extract of the stem bark of Bombacopsis glabra (Bombacaceae). The structures were determined by 13C and ¹H NMR (1D and 2D) and mass spectrometry, and by comparison with literature data for triterpenes. The structure of the flavone 1 was unambiguously confirmed by a X-ray diffraction study. The five substances were isolated for the first time from Bombacaceae species.